SIV-specific CD8+ T cells express high levels of PD1 and cytokines but have impaired proliferative capacity in acute and chronic SIVmac251 infection. - Petrovas, C; Price, D; Mattapallil, J; Ambrozak, DR; Geldmacher, C; Cecchinato, V; Vaccari, M; Tryniszewska, E; Gostick, E; Roederer, M; Douek, D; Morgan, S; et al. (2007)
Programmed death-1 (PD-1) is a critical mediator of virus-specific CD8+ T-cell exhaustion. Here, we examined the expression of PD-1 on simian immunodeficiency virus (SIV)-specific CD8+ T cells and its possible involvement in regulation of cytokine production, proliferation, and survival of these cells. The majority of SIV-specific CD8+ T cells expressed a PD-1(high) phenotype, independent of their differentiation status, in all tissues tested. PD-1 expression gradually declined on CD8+ T cells specific for SIV-derived epitopes that had undergone mutational escape, indicating that antigen-specific TCR stimulation is the primary determinant of PD-1 expression. SIV-specific PD-1(high)CD8+ T cells produced IFN-gamma, TNF-alpha, and IL-2 under cognate peptide stimulation. While CD8+ T cells that proliferated in response to antigen had a PD-1(high) phenotype, it was determined that there was a reduced proliferative capacity of PD-1(high) compared with PD-1(low) SIV-specific CD8+ T cells. PD-1(high) SIV-specific CD8+ T cells were highly susceptible to cell death leading to loss of such cells after in vitro stimulation. Thus, PD-1 is a negative regulator of SIV-specific CD8+ T cells, operating predominantly through the induction of cell death. Manipulation of the interaction of PD-1 with its ligands could thus potentially restore the CD8+ T-cell responses in SIV infection.